2022
DOI: 10.1111/add.15823
|View full text |Cite
|
Sign up to set email alerts
|

Drug Overdoses During the COVID‐19 Pandemic Among Recently Homeless Individuals

Abstract: Aims To examine how weekly rates of emergency department (ED) visits for drug overdoses changed among individuals with a recent history of homelessness (IRHH) and their housed counterparts during the pre‐pandemic, peak, and re‐opening periods of the first wave of the COVID‐19 pandemic, using corresponding weeks in 2019 as a historical control. Design Population‐based retrospective cohort study conducted between September 30, 2018 and September 26, 2020. Setting Ontario, Canada. Participants A total of 38 617 I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Shelters are high risk settings for COVID-19 outbreak due to the crowded and communal environment, as well as the higher rates of comorbidities among people deprived of housing. Homeless individuals in one Canadian study were disproportionately impacted by overdoses during reopening compared to those individuals with stable housing [ 2 ]. Shelter-in-place orders, in the USA, were associated with a higher risk of emergency room visits for overdose [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shelters are high risk settings for COVID-19 outbreak due to the crowded and communal environment, as well as the higher rates of comorbidities among people deprived of housing. Homeless individuals in one Canadian study were disproportionately impacted by overdoses during reopening compared to those individuals with stable housing [ 2 ]. Shelter-in-place orders, in the USA, were associated with a higher risk of emergency room visits for overdose [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This incline in opioid‐related deaths attributed to people experiencing homelessness has also outpaced the increase in the number of people experiencing homelessness in Canada, which has been estimated to have grown by 12% from 2018 to 2022 [7]. This study adds to other research showing that PEH have been harmed disproportionately by the opioid poisoning epidemic, and particularly so during the COVID‐19 pandemic [3, 27].…”
Section: Discussionmentioning
confidence: 79%
“…Drawing upon coroner and medical examiner data, this report found that among Canadians who died of a drug toxicity in the 2‐year period, 7.8% were experiencing homelessness at the time of death. However, these findings probably no longer represent the current landscape of substance‐related harms, which has been further exacerbated by the COVID‐19 pandemic and a variety of changes in other social and environmental factors [3, 21–28]. As a priority population, which has already experienced disproportionate effects of the pandemic [29, 30], deeper examination of the intersection of PEH, opioid‐related overdose deaths and the contextual details surrounding these fatal events is critical to inform supportive measures and policies towards harm reduction and housing solutions in the COVID era.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…People using illicit opioids experience a high burden of disease [17,18] and may be disproportionately impacted by major disruptive events such as a pandemic [19,20], particularly when facing other challenges such as housing instability [21,22]. Apart from risks related to COVID-19 exposure [23], public health responses to the pandemic directly impacted the risk environment shaping drug-related harms [24]: many low-threshold services that people with OUD rely on to meet essential needs or reduce harms associated with drug consumption, such as day shelters and supervised consumption sites, were forced to temporarily close or reduce their capacity, making already scarce resources even less accessible, while pandemic-related prevention measures also affected people's ability to generate income, secure shelter, and obtain safe and secure supplies of drugs [25][26][27][28][29].…”
Section: People With Oud the Covid-19 Pandemic And Oat Delivery Via T...mentioning
confidence: 99%